Общественные блага и трагедия общин – проблема общей собственности - Siebers, Adrianna (Przegląd Prawniczy Uniwersytetu im. Adam Mickiewicza, 2015)
The aim of the study is to evaluate the selected issues concerned with the functioning of the notion of common good in relation to the co-ownership. The author presents the construction of this two forms with a special emphasis on the social aspect of the common good in the public space.